Evaluation of bioactive compounds, pharmaceutical quality, and anticancer activity of curry leaf (Murraya koenigii L.) - Ghasemzadeh, Ali; Jaafar, Hawa Z. E.; Rahmat, Asmah; Devarajan, Thiyagu (Hindawi Publishing Corporation, 2014)
In this study, we investigated some bioactive compounds and pharmaceutical qualities of curry leaf (Murraya koenigii L.) extracts from three different locations in Malaysia. The highest TF and total phenolic (TP) contents were observed in the extracts from Kelantan (3.771 and 14.371 mg/g DW), followed by Selangor (3.146 and 12.272 mg/g DW) and Johor (2.801 and 12.02 mg/g DW), respectively. High quercetin (0.350 mg/g DW), catechin (0.325 mg/g DW), epicatechin (0.678 mg/g DW), naringin (0.203 mg/g DW), and myricetin (0.703 mg/g DW) levels were observed in the extracts from Kelantan, while the highest rutin content (0.082 mg/g DW) was detected in the leaves from Selangor. The curry leaf extract from Kelantan exhibited higher concentration of gallic acid (0.933 mg/g DW) than that from Selangor (0.904 mg/g DW) and Johor (0.813 mg/g DW). Among the studied samples, the ones from Kelantan exhibited the highest radical scavenging activity (DPPH, 66.41%) and ferric reduction activity potential (FRAP, 644.25 μm of Fe(II)/g) followed by those from Selangor (60.237% and 598.37 μm of Fe(II)/g) and Johor (50.76% and 563.42 μm of Fe(II)/g), respectively. A preliminary screening showed that the curry leaf extracts from all the locations exhibited significant anticarcinogenic effects inhibiting the growth of breast cancer cell line (MDA-MB-231) and maximum inhibition of MDA-MB-231 cell was observed with the curry leaf extract from Kelantan. Based on these results, it is concluded that Malaysian curry leaf collected from the North (Kelantan) might be potential source of potent natural antioxidant and beneficial chemopreventive agents.